2015
DOI: 10.1051/0004-6361/201425271
|View full text |Cite
|
Sign up to set email alerts
|

2D He+pickup ion velocity distribution functions: STEREO PLASTIC observations

Abstract: Context. He+ pickup ions are either born from the ionization of interstellar neutral helium inside our heliosphere, the so-called interstellar pickup ions, or through the interaction of solar wind ions with small dust particles, the so-called inner source of pickup ions. Until now, most observations of pickup ions were limited to reduced 1D velocity spectra, which are insufficient to study certain characteristics of the He + velocity distribution function (VDF). Aims. It is generally assumed that rapid pitch-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 42 publications
1
27
0
Order By: Relevance
“…While traveling outward with the solar wind, the initial anisotropic VDF is gradually transformed into an isotropic VDF by pitch-angle scattering, which until recently was expected to be a rapid process. However, independent observations made by different spacecraft showed that in particular the He + VDF remains anisotropic for much longer than previously assumed (Oka et al 2002;Drews et al 2015;Taut et al 2016).…”
Section: Pickup Ion Cutoffmentioning
confidence: 83%
See 2 more Smart Citations
“…While traveling outward with the solar wind, the initial anisotropic VDF is gradually transformed into an isotropic VDF by pitch-angle scattering, which until recently was expected to be a rapid process. However, independent observations made by different spacecraft showed that in particular the He + VDF remains anisotropic for much longer than previously assumed (Oka et al 2002;Drews et al 2015;Taut et al 2016).…”
Section: Pickup Ion Cutoffmentioning
confidence: 83%
“…We define the ideal torus as the theoretical velocity-space trajectory that an injected PUI with initial speed V n = 0 would follow under a perfectly stable IMF configuration. Former PUI studies (e.g., Drews et al 2015Drews et al , 2016 and also Möbius et al (2015) restrict the IMF data to orientations that lie ±20 • within the ecliptic plane. Then it solely depends on the azimuthal angle of the IMF whether an ideal torus falls into PLASTIC's FoV or not.…”
Section: Pickup Ion Cutoffmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, a ratio of R(w sw ) = 3 implies that only ∼50% of the observed pickup ions are distributed isotropically in phase space. However, this is based on the assumption that (1) the anisotropic state of the pickup ion VDF is solely caused by the initial pickup ion torus distribution, and that the torus distribution behaves as described in Drews et al (2015). This means that (2) the inclination of the torus systematically changes with the orientation of B; (3) it does not change in intensity as a function of its orientation and especially that (4) a torus distribution is a common feature neither confined to special heliospheric conditions nor individual pickup ion species.…”
Section: Discussionmentioning
confidence: 99%
“…As described in Drews et al (2015), the observation of a torus or ring-beam signature of He + pickup ions is confined to specific configurations of the local magnetic field vector. These configurations depend mainly on the angular acceptance of the observing instrument.…”
Section: Methodsmentioning
confidence: 99%